Umetna inteligenca in pravice iz ustvarjalnosti - Damjan, Matija (Podjetje in delo, 2023)
Generative artificial intelligence (AI) can generate texts, images or other media at the user's prompt. The paper examines whether and how intellectual property rights protect AI products. Copyright, a potential new AI producer's right and patents for AI-generated inventions come into play. Another question addressed is how generative artificial intelligence interferes with the rights of human creators if it learns to imitate their style through machine learning on existing works of authorship and if it generates an actor's performance in a new film role from an existing recording of the actor's image and voice.
Keywords: Avtorske pravice; generativna umetna inteligenca; Intelektualna lastnina; izvajalci; patenti; sorodne pravice; strojno učenje; Umetna inteligenca